Answer:
(4, 0)
Step-by-step explanation:
given the 2 equations
y = x - 4 → (1)
- 4x - 6y = - 16 → (2)
substitute y = x - 4 into (2)
- 4x - 6(x - 4) = - 16
- 4x - 6x + 24 = - 16
- 10x + 24 = - 16 ( subtract 24 from both sides )
- 10x = - 40 ( divide both sides by - 10 )
x = 4
substitute x = 4 into (1) for corresponding value of y
y = 4 - 4 = 0
solution is (4, 0)
Answer:
x = 15 or x = - ![\frac{2}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7D)
Step-by-step explanation:
Cross- multiplying gives
(14x + 6)(17x + 5) = 9x(27x + 11) ( expanding factors )
238x² + 172x + 30 = 243x² + 99x
rearrange into standard form : ax² + bx + c = 0
5x² - 73x - 30 = 0 ← in standard form
consider the factors of the product 5 × - 30 = - 150 which sum to the coefficient of the x-term (- 73 )
the factors are - 75 and + 2
Use these factors to split the middle term
5x² - 75x + 2x - 30 = 0 ( factor by grouping )
5x(x - 15) + 2(x - 15) = 0 ← take out the factor (x - 15)
(x - 15)(5x + 2) = 0
equate each factor to zero and solve for x
x - 15 = 0 ⇒ x = 15
5x + 2 = 0 ⇒ x = - ![\frac{2}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B5%7D)
Answer:
i think it is A, C, OR B, **For the first equation**
Step-by-step explanation:
SRRY IF WRONG!
Since angles 3 and 4 are supplementary, they add up to 180 degrees.
Angle 3 is 88 degrees.
To get the measure of the last angle, let's subtract 88 from 180.
180 - 88 = 92
Thus, Angle 4 has a measure of 92 degrees.
Have an awesome day! :)
Answer:
i think the answer would be B i think if its wrong i am sorry
Step-by-step explanation: